PERBAIKAN MANAJEMEN PERGUDANGAN DI PERUSAHAAN PENERBANGAN NASIONAL MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS - Jhonny P. Simbolon; Sawarni Hasibuan (Universitas Mercu Buana, 2017)
The warehouse is one part of the supply chain that plays an important role in PT. Garuda Maintenance Facility (GMF), because the warehouse stores the components of the material used for aircraft maintenance activities. However, a number of problems in the warehouse caused the process in the warehouse to be less than optimal. The purpose of this study was to analyze the potential for improvement of warehousing management at PT. GMF. In the early stages, fishbone diagrams are used to identify the main causes of problems that occur in PT. GMF is related to five factors, namely the labor factor (man), method (method), material, machine (equipment), and environment. Furthermore, a failure mode and effect analysis (FMEA) approach is implemented to get priority improvements. The results of the analysis found that the use of wireless technology, the application of capacity check functions and monitoring and training functions are needed to improve warehousing management at PT. Garuda Maintenance Facility.